The Oxford handbook of ecclesiology - Avis, Paul (Oxford University Press, 2018)
Nearly thirty expert contributions describe the continuities and discontinuities in the changing understanding of the church in this comprehensive resource for the scholarly study of the theological identity and self-understanding of the church through the centuries. The scope of ecclesiology is defined by the manifold self-understanding and action of the church in relation to a number of research fields, including its historical origins, structures of authority, doctrine, ministry and sacraments, unity and diversity, and mission, as well as its relation to the state, to civil society, and to culture. The book covers the main sources of such ecclesiological research and reflection, namely the Bible, church history from the apostolic age to the present, the wealth of the Christian theological traditions, the experience and practice of the churches today, together with information and insights that emerge from other relevant academic disciplines.
Keywords: Aufsatzsammlung; Ekklesiologie